Effect of tillage and irrigation on yield and soil properties under rice (Oryza sutiva)-wheat (Triticumz aestivum) system on a sandy clay loam soil of Uttaranchal - BHATTACHARYYA, RANJAN; SINGH, R D; CHANDRA, S; KUNDU, S; GUPTA, H S (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted for 2 years (2001-02 to 2002-03) to study the tillage (conventional and zero) and irrigations effects on direct seeded rice (Oryza Sativa L.) wheat (Triticulil aestivunl L. emend. Fiori & Paol.)productivity and soil physical conditions after ricc and wheat harvest. Tl crew as a reduction up to 6% in soil organic carbon with conventional tillage both aftcr rice and wheat halvest. Soil organic carbon increased (data) significant with incrcase in levels of irrigation for both tlie crops and the hiegst average value of organic carbon obtained in the most frequently irrigated plots. Soil bulk density decreased significantly with conventional tillage ( 1.34 and 1.36 MgIm3 at 0-1 5 and 15-30 cm soil depth respectively) at both the soil depths and after botli rice and wheat crop. But plant available water capacity was significantly higher in zero tilled plots (5.07 and 4.86 cnu’ 30 c ns o il layer after rice and wheat crop respectively) tlian the conventionally tilled plots (4.23 and 4.21 cni 130 cm soil layer after rice and wheat crop respectively). There was a significant increase in labo .atorye stimated saturated hydraulic conductivity ncasurcdu ndcr zero-tilled plots (1 .I3 and 1.07 cn ihart 0-15 and 15-30 cm soil layer respectively) after rice harvest. Pooled yield data sliowcd that the performance of conventionally and zcro-tilled direct seeded rice was at par but botli rice and wheat yields were 1 and 4’s higher respcctively in conventionaliy tilled plots.